(untitled) (Global Journal of Human-Social Science, 2024)
This study focuses on the effects of government expenditure on human capital training in the Cameroon education system The work is based on the experience of secondary education system and accesses the efficacy based on the school dropout rate The descriptive and econometric statistics used on this topic come from the Public Expenditure Tracking Survey carried out in 2019 by the INS The results of the findings enabled us to conclude that government expenditure as far as education is concerned is very helpful in human capital training because it reduces the rate of school dropout in Cameroon In other words government spending helps to reduce school disparities in rural and urban areas improves the quality of educational infrastructure and the living standards of teachers